1978
DOI: 10.1116/1.569696
|View full text |Cite
|
Sign up to set email alerts
|

UPS and LEED studies of GaAs (110) and (111) As surfaces

Abstract: By comparison of LEED intensity–voltage data on GaAs (110) surfaces prepared by cleaving and by chemical etch followed by sputter annealing, we find the surfaces to be essentially the same in atomic geometry within the limits of experimental error. However, we find that important distinctions can be made between (110) surfaces prepared by these two methods when Fermi-energy pinning and UPS data are considered. In this regard, we show that Fermi-energy pinning is a particularly sensitive indicator of the degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…For calculations of bulk GaAs, the integration over the Brillouin zone was performed using a k-points grid of 8 × 8 × 8 during the cell optimization and electronic properties calculations. We have obtained a lattice constant of a = 5.543 Å, which is close to the experimental value of a = 5.653 Å. GaAs( 110) and (111)B surface orientations were selected to study the effects of surface polarity; they are stable surfaces observed in the experiments, 46,47 110) and (111)B surfaces and GaAs/P3HT interfaces. All surface and interface geometries were optimized with the method of Broyden−Fletcher−Goldfarb−Shanno (BFGS) until all of the forces on all atoms became lower than 0.02 eV/Å and total energy difference between two optimization steps of the minimization procedures was <10 −4 eV.…”
Section: ■ Experimental Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…For calculations of bulk GaAs, the integration over the Brillouin zone was performed using a k-points grid of 8 × 8 × 8 during the cell optimization and electronic properties calculations. We have obtained a lattice constant of a = 5.543 Å, which is close to the experimental value of a = 5.653 Å. GaAs( 110) and (111)B surface orientations were selected to study the effects of surface polarity; they are stable surfaces observed in the experiments, 46,47 110) and (111)B surfaces and GaAs/P3HT interfaces. All surface and interface geometries were optimized with the method of Broyden−Fletcher−Goldfarb−Shanno (BFGS) until all of the forces on all atoms became lower than 0.02 eV/Å and total energy difference between two optimization steps of the minimization procedures was <10 −4 eV.…”
Section: ■ Experimental Methodssupporting
confidence: 74%
“…For calculations of bulk GaAs, the integration over the Brillouin zone was performed using a k -points grid of 8 × 8 × 8 during the cell optimization and electronic properties calculations. We have obtained a lattice constant of a = 5.543 Å, which is close to the experimental value of a = 5.653 Å. GaAs(110) and (111)B surface orientations were selected to study the effects of surface polarity; they are stable surfaces observed in the experiments, , and both top layers terminate with As atoms. For the calculations of the GaAs slabs, in-plane lattice parameters of GaAs(110) and GaAs(111)B surfaces were obtained from optimization of the corresponding bulk GaAs.…”
Section: Experimental Methodssupporting
confidence: 73%
“…The clean Ge͑100͒ and Ge͑111͒ surfaces showed the characteristic low energy electron diffraction ͑LEED͒ patterns of the ͑2 ϫ 1͒ and c͑2 ϫ 8͒ reconstructions, respectively, in agreement with literature data. 22,23 GaAs͑110͒ also showed the expected ͑110͒ LEED pattern, 24 but the precise stoichiometry of the surface remained undetermined, as preferential sputtering of As is likely to lead to Ga-rich surface layers. After cleaning, no surface oxidation was detected by x-ray absorption spectra ͑XAS͒ at the oxygen K edge.…”
mentioning
confidence: 99%
“…Surface photovoltage spectroscopy was used to demonstrate photo-induced transitions between surface state levels and the subsequent ejection of electrons into the conduction band (295). The degree of surface perfection of GaAs(llO) surfaces prepared by cleaving and by chemical etching followed by sputter annealing was measured using LEED and UPS (370). The electronic and geometrical structure of the cleaved GaAs(llO) surface was measured using UPS (321); models of the surface Ga and As atom motion are proposed.…”
Section: Semiconductorsmentioning
confidence: 99%